Resin composition, prepreg, resin film, metal-clad laminate, printed wiring board, and semiconductor package
By using resin compositions containing ethylene base and rings with a heavy average molecular weight of 50,000 or more, the problem of resin materials in electronic equipment in the electronic equipment in high frequent application intermediary electrical characteristics and process efficiency, realizing low mediaties constant and The effect of low -profile electric losses consumes a positive corner.
Patent Information
- Application Number
- CN202480002217.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-24
- Filing Date
- 2024-05-22
- Publication Date
- 2025-01-24
AI Technical Summary
In electronic devices, especially in high frequency band applications, existing resin materials are difficult to meet the requirements of low dielectric constant and low dielectric loss tangent at the same time, resulting in high transmission losses and overlapping of prepregs and resin films It is difficult to peel off during the time, affecting process efficiency.
Using a curable prepolymer containing vinyl benzyl and indene rings, a resin composition with a weight average molecular weight of more than 50,000 is used to improve the viscosity of the coating and the formability of the cured product, thereby improving the performance of printed circuit boards and metal-clad laminates. performance.
The dielectric constant and dielectric loss tangent are reduced, the viscosity and formability of the resin composition are improved, the transmission loss is reduced, the process flow is simplified, and the problem of difficult peeling of prepreg and resin film is avoided.
Smart Images

Figure BDA0005088864560000051 
Figure BDA0005088864560000061 
Figure BDA0005088864560000062
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a prepreg, a resin film, a metal-clad laminate, a printed wiring board and a semiconductor package. Background Art
[0002] Metal-clad laminates represented by copper-clad laminates, prepregs that can be used for metal-clad laminates, semiconductor packages using metal-clad laminates, etc. are used in mobile communication devices such as smartphones, their base station devices, servers, routers, large servers and other network infrastructure equipment, large computers, personal computers, industrial computers and other electronic devices. In addition, they are also used in electronic devices installed in home appliances, automobiles, etc. Among them, the demand for electronic communication equipment to process large amounts of data at high speed has increased due to the popularization of 5G.
[0003] In electronic devices, when processing a large amount of data at high speed, substrate materials with low transmission loss in the high-frequency region are required. The substrate material uses a resin with a low dielectric constant and a low dielectric loss tangent to provide a substrate with low transmission loss, but due to the development of communication technology in recent years, there is a further demand for the development of resins with low dielectric constants and low dielectric loss tangents.
[0004] Patent Document 1 discloses a thermosetting resin composition containing a vinylbenzyl compound and a polycarbodiimide compound as a material for electronic components used in high frequency bands, and proposes that the obtained electronic component has improved adhesion to metal materials while maintaining excellent dielectric properties.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2007-119531 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The signals used in mobile communication devices such as smartphones, their base station devices, network infrastructure equipment such as servers and routers, and electronic devices such as large computers are becoming faster and more capacitive every year. Along with this, the printed circuit boards installed in these electronic devices need to cope with high frequencies, requiring dielectric properties that can reduce transmission losses, and substrate materials with low dielectric constants and low dielectric loss tangents.
[0010] In patent document 1, a resin composition containing vinylbenzyl compounds and polycarbodiimide compounds with dielectric properties suitable for high-frequency band applications is disclosed. However, the inventors have further studied and found that there is a trend: if a plurality of prepregs or resin films formed by using such a resin composition containing vinylbenzyl compounds are overlapped, they are closely fitted to each other and difficult to peel off. Therefore, in the transportation of prepregs and the manufacture of metal-clad laminates, it is worried that the workability is reduced. In addition, the formability of metal-clad laminates also has room for improvement.
[0011] An object of the present invention is to provide a resin composition having improved adhesion of a coating material and moldability of a cured product, and a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package obtained using the resin composition.
[0012] Means for solving problems
[0013] The present invention includes the following embodiments. However, the present invention is not limited to the following embodiments.
[0014] One embodiment relates to a resin composition including a curable prepolymer having a vinylbenzyl group and an indene ring and having a weight average molecular weight of 50,000 or more.
[0015] Effects of the Invention
[0016] According to the present invention, there can be provided a resin composition having improved adhesion of a coating material and moldability of a cured product, and a prepreg, a resin film, a metal-clad laminate, a printed wiring board, and a semiconductor package obtained using the resin composition. DETAILED DESCRIPTION
[0017] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.
[0018] In the present invention, the numerical range represented by "~" indicates a range including the numerical values recorded before and after "~" as the minimum value and the maximum value, respectively. In the numerical range recorded in stages in the present invention, the upper limit or lower limit of a certain numerical range can be replaced by the upper limit or lower limit of other numerical ranges. In addition, the upper limit or lower limit of the numerical range recorded in the present invention can be replaced by the value shown in the embodiment. In the present invention, unless otherwise specified, each component may contain one or more corresponding substances. In the present invention, regarding the content of each component in the resin composition, when there are multiple substances equivalent to each component in the resin composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the resin composition.
[0019] In the present invention, unless otherwise specified, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are numerical values measured by the following steps. The weight average molecular weight and the number average molecular weight are converted by gel permeation chromatography (GPC) according to a standard curve using standard polystyrene. The standard curve uses 5 sample groups (PStQuick MP-H, PStQuickB [Tosoh Corporation, trade name]) of standard polystyrene and is approximated by a cubic formula. The conditions of GPC are shown below.
[0020] Device: High-speed GPC device "HLC-8320GPC" (Tosoh Corporation, trade name)
[0021] Detector: Ultraviolet absorption detector "UV-8320" (Tosoh Corporation, trade name)
[0022] Column: guard column; TSKgel guardcolumn Super(HZ)-M+, column; TSKgel SuperMultiporeHZ-M (2 pieces), reference column; TSKgel SuperH-RC (2 pieces) (all Tosoh Corporation, trade names)
[0023] Column size: 4.6×20mm (guard column), 4.6×150mm (column), 6.0×150mm (reference column)
[0024] Eluent: Tetrahydrofuran
[0025] Sample concentration: 10mg / 1mL
[0026] Injection volume: 20μL or 2μL
[0027] Flow rate: 0.35mL / min
[0028] Measurement temperature: 40℃
[0029] "Resin composition"
[0030] The resin composition of one embodiment includes a curable prepolymer having a weight average molecular weight of 50,000 or more and containing a vinylbenzyl group and an indene ring. Hereinafter, the curable prepolymer having a weight average molecular weight of 50,000 or more and containing a vinylbenzyl group and an indene ring may be simply referred to as a curable prepolymer.
[0031] The curable prepolymer is a prepolymer in which a part of the vinylbenzyl group having a polymerizable reactive group does not participate in the polymerization reaction and remains. By making the curable prepolymer have a vinylbenzyl group, curing is accelerated by using heating, pressurization, a curing accelerator, etc., so that a cured product can be obtained. In order to be able to apply the curable prepolymer to a substrate and the like for forming, it is preferred that the curable prepolymer itself is liquid, or the curable prepolymer is dissolved or dispersed in a solvent to become a liquid composition.
[0032] The weight average molecular weight (Mw) of the curable prepolymer is preferably more than 50,000, more preferably more than 100,000, more than 150,000 or more than 300,000. In these ranges, the adhesion of the surface of the coating of the resin combination can be more appropriately suppressed. For example, the viscosity of the coatings such as prepregs and resin films can be further improved. When mixed with other components, the compatibility of the curable prepolymer and elastomers can be better maintained. In addition, when the coating of the resin combination is cured, the separation of the resin can be further suppressed. For example, in cured products such as metal-clad laminates, the layer separation of the resin can be further suppressed.
[0033] The weight average molecular weight (Mw) of the curable prepolymer is not particularly limited, and for example, may be 500,000 or less. From the viewpoint of inhibiting the gelation and coating properties of the resin composition, the weight average molecular weight (Mw) of the curable prepolymer may be 250,000 or less, 200,000 or less, or 150,000 or less. In addition, within these ranges, there is also the advantage that the solution viscosity of the synthesis system can be better maintained when synthesizing the curable prepolymer.
[0034] For example, the weight average molecular weight (Mw) of the curable prepolymer may be 50,000 to 500,000, 100,000 to 250,000, or 150,000 to 200,000. On the other hand, from the viewpoint of the viscosity of the coating and the formability of the cured product, the weight average molecular weight (Mw) of the curable prepolymer is preferably 150,000 to 500,000, or 300,000 to 500,000. The method for measuring the weight average molecular weight (Mw) of the curable prepolymer is based on the method described above.
[0035] The curable prepolymer contains a vinylbenzyl group and an indene ring. For example, a prepolymer containing a structural unit containing a vinylbenzyl group and a structural unit containing an indene ring, a prepolymer containing a vinylbenzyl group and an indene ring as substituents in the skeleton of the prepolymer, a prepolymer containing an indene ring as a substituent in the skeleton of a prepolymer containing a structural unit containing a vinylbenzyl group, a prepolymer containing a vinylbenzyl group as a substituent in the skeleton of a prepolymer containing a structural unit containing an indene ring, a prepolymer containing a structural unit containing a vinylbenzyl group and an indene ring, etc. can be mentioned.
[0036] The curable prepolymer is preferably a prepolymer containing a structural unit having a vinylbenzyl group and an indene ring, and more preferably a prepolymer containing a structural unit having an indene ring and a vinylbenzyl group directly bonded to a carbon atom of the indene ring.
[0037] In the curable prepolymer, the indene ring may be unsubstituted or may have a substituent. For example, the indene ring is represented by the following formula (1).
[0038] [Chemical formula 1]
[0039]
[0040] In formula (1), R 1 and R 4 Each R is independently a hydrogen atom, a halogen atom, a monovalent organic group, or a group having a bonding site with another structure. 1 and R 4 The monovalent organic group shown may be an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a thioalkoxy group having 1 to 5 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. The halogen atom may be a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. In formula (1), R 1 and R 4 At least one of R may be a vinylbenzyl group. 1 and R 4 At least one of the R is a group having a bonding site with another structure. 1 and R 4 The respective groups may be entirely the same or partially or entirely different. The benzene ring of the indene ring may be unsubstituted.
[0041] In addition, R present in the curable prepolymer 1 and R 4 At least one of the groups may be an arylalkyl group other than the vinylbenzyl group, and the arylalkyl group may not have a polymerizable unsaturated bond.
[0042] The indene ring can be represented by the following formula (1a).
[0043] [Chemical formula 2]
[0044]
[0045] In formula (1a), R 1 and R 4 can be independently the groups listed in the above formula (1), R 2 and R 3 can be independently R in the above formula (1) 1 The groups listed in R 1 ~R 3 They may be all the same, or they may be partially or completely different. 4 They may be all the same or partly or entirely different. The benzene ring of the indene ring may be unsubstituted.
[0046] In the curable prepolymer, the vinylbenzyl group may be unsubstituted or may have a substituent. For example, the vinylbenzyl group is represented by the following formula (2).
[0047] [Chemical formula 3]
[0048]
[0049] In formula (2), R 5 is a hydrogen atom, a halogen atom, or a monovalent organic group. 5 The monovalent organic group shown may be an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a thioalkoxy group having 1 to 5 carbon atoms, or an aryl group having 6 to 20 carbon atoms. The halogen atom may be a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom. 5 The vinylbenzyl groups may be all the same or some or all may be different. The vinylbenzyl group may be unsubstituted.
[0050] For the curable prepolymer, in formula (1), R 1 At least one of the R may be a vinylbenzyl group. 1 At least one of the groups may be a group containing a bonding site with another structure. For the curable prepolymer, in formula (1), R 1 At least one of them may be a vinylbenzyl group, and the remaining R 1 At least one of them may be a group including a bonding site to another structure.
[0051] In addition, R present in the curable prepolymer 1 At least one of the groups may be an arylalkyl group other than the vinylbenzyl group, and the arylalkyl group may not have a polymerizable unsaturated bond.
[0052] The curable prepolymer may include a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group, and a vinylbenzyl group further bonded to the indenyl group, or may include a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group at any of the 1-position, 2-position and 3-position, and a vinylbenzyl group bonded to at least one of the remaining 1-position, 2-position and 3-position of the indenyl group.
[0053] The curable prepolymer may include a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group, and a vinylbenzyl group further bonded to the indenyl group; and a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group, and an arylalkyl group other than the vinylbenzyl group further bonded to the indenyl group, and the arylalkyl group may not have a polymerizable unsaturated bond. The curable prepolymer may include a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group at any position among the 1-position, 2-position, and 3-position, and a vinylbenzyl group bonded to at least one of the remaining 1-position, 2-position, and 3-position of the indenyl group; and a structure having a methylphenyl group, an indenyl group bonded to the methyl group of the methylphenyl group at any position among the 1-position, 2-position, and 3-position, and an arylalkyl group other than the vinylbenzyl group bonded to at least one of the remaining 1-position, 2-position, and 3-position of the indenyl group, and the arylalkyl group may not have a polymerizable unsaturated bond.
[0054] The 1-position, 2-position and 3-position of the indenyl group and the indene ring are shown below.
[0055] [Chemical formula 4]
[0056]
[0057] For example, the curable polymer may include a structural unit represented by the following formula (3).
[0058] [Chemical formula 5]
[0059]
[0060] In formula (3), R 6 is unsubstituted or substituted indenyl. 5 It can be the groups listed in formula (2). 5 A part or all of them may be hydrogen atoms. For example, the curable polymer may include a structural unit represented by the following formula (4).
[0061] [Chemical formula 6]
[0062]
[0063] In formula (4), R 1 and R 4 can be independently the groups listed in formula (1), R5 It can be the groups listed in formula (2). 1 At least one of them may be an unsubstituted or substituted vinylbenzyl group. 1 At least one of them may be a group having a bonding site with another structure. 4 and R 5 Some or all of them may be hydrogen atoms.
[0064] In addition, R present in the curable prepolymer 1 At least one of the groups may be an arylalkyl group other than the vinylbenzyl group, and the arylalkyl group may not have a polymerizable unsaturated bond.
[0065] The curable prepolymer can be a polymer of a monomer. As a monomer, for example, a monomer having one or more vinylbenzyl groups, a monomer having one or more indene rings, a monomer having one or more vinylbenzyl groups and indene rings, etc. can be cited. The polymerization is not completely completed, and the polymerization can be stopped when the vinylbenzyl groups from the monomers remain to a certain extent. For example, in order to obtain a curable prepolymer in a liquid state, the polymerization can be stopped when the viscosity of the polymerization reaction system of the curable prepolymer reaches a certain degree. An oligomer can be used together with a monomer or in place of a monomer.
[0066] Curable prepolymers can be, for example, polymers comprising structural units from vinylbenzyl compounds, wherein the vinylbenzyl compounds have vinylbenzyl and indene rings in one molecule. The vinylbenzyl compound can be a monomer, an oligomer or a combination thereof, preferably a monomer from the viewpoint of molecular design. Hereinafter, vinylbenzyl compounds having vinylbenzyl and indene rings are sometimes referred to as vinylbenzyl compounds. Curable prepolymers can have only structural units from the same vinylbenzyl compound, or structural units from a variety of vinylbenzyl compounds.
[0067] The vinylbenzyl compound may be a compound having one or more vinylbenzyl groups and one or more indene rings in one molecule, or a compound having one or more vinylbenzyl groups and one indene ring in one molecule, or a compound having 1 to 3 vinylbenzyl groups and one indene ring in one molecule. The vinylbenzyl compound may be a compound in which the vinylbenzyl group is directly bonded to a carbon atom of the indene ring.
[0068] In addition, the vinylbenzyl compound may be a compound having one or more vinylbenzyl groups, one or more indene rings, and one or more arylalkyl groups other than the vinylbenzyl group in one molecule. It may also be a compound having one or more vinylbenzyl groups, one indene ring, and one or more arylalkyl groups other than the vinylbenzyl group in one molecule. The vinylbenzyl compound may be a compound in which the vinylbenzyl group and the arylalkyl group other than the vinylbenzyl group are directly bonded to the carbon atom of the indene ring. The arylalkyl group other than the vinylbenzyl group may not have a polymerizable unsaturated bond.
[0069] The curable prepolymer may be a polymer comprising a structural unit derived from a compound having an indene ring and having 1 to 3 vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring, or may be a polymer comprising a structural unit derived from a compound having 2 to 3 vinylbenzyl groups bonded to the 1-position, 2-position and 3-position of the indene ring.
[0070] In addition, the curable prepolymer may be a polymer containing a structural unit derived from a compound having an indene ring, having 1 or 2 vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring, and having 1 or 2 arylalkyl groups other than the vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring. In addition, it may be a polymer containing both structural units derived from a compound having an indene ring, having 1 to 3 vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring, and having no arylalkyl groups other than the vinylbenzyl groups, and structural units derived from a compound having an indene ring, having 1 or 2 vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring, and having 1 or 2 arylalkyl groups other than the vinylbenzyl groups bonded to any of the 1-position, 2-position and 3-position of the indene ring.
[0071] In the polymerization using such a monomer, a curable prepolymer is obtained in an incomplete polymerization state, so that in the curable prepolymer, a part of the vinylbenzyl groups of the monomer participate in the polymerization to form the skeleton of the prepolymer, and another part of the vinylbenzyl groups of the monomer do not participate in the polymerization and exist in the curable prepolymer as vinylbenzyl groups.
[0072] In the vinylbenzyl compound, the indene ring and the vinylbenzyl group may be unsubstituted or may have a substituent. The substituent of the indene ring may be R in the above formula (1) and formula (2): 1 and R 4 As a substituent of the vinylbenzyl group, R in the above formula (3) may be 5 The groups listed in .
[0073] The vinylbenzyl compound may be a compound represented by the following formula (5-1) or (5-2).
[0074] [Chemical formula 7]
[0075]
[0076] In formula (5-1), n is an integer of 1 to 3. n is more preferably 2 or 3, and more preferably 2. It should be noted that the resin composition containing the curable prepolymer may contain a curable prepolymer that is a copolymer of multiple monomers with different n. In this case, n is preferably 1 to 3 on average, more preferably 2 to 3, and further preferably 2.0 to 2.5. It should be noted that in formula (5-1), the indene ring and the vinylbenzyl group may each have a substituent.
[0077] In formula (5-1), the vinylbenzyl group may be directly bonded to a carbon atom at any of the 1-position, 2-position, and 3-position of the indene ring, but is preferably bonded to the 1-position, or a combination of the 1-position and the 3-position. One or two vinylbenzyl groups may be bonded to each position. For example, the vinylbenzyl group may be bonded to the 1-position, the combination of the 1'-position, and the 3-position of the indene ring, or the combination of the 1-position and the 1'-position of the indene ring.
[0078] In formula (5-1), the methyl group of the vinylbenzyl group may be in any of the ortho, meta and para positions, preferably in the meta or para position. When the polymer is obtained using two or more monomers, it may be a mixture of an ortho-body, a meta-body and a para-body. In this case, a combination of a meta-body and a para-body is preferred, and the mass ratio of the meta-body to the para-body is preferably 40:60 to 60:40.
[0079] In formula (5-2), R 7 is a hydrogen atom or a saturated hydrocarbon group having 1 to 6 carbon atoms. 7 It may be an alkyl group having 1 to 3 carbon atoms. Hereinafter, the following structural part in formula (5-2) may be referred to as "arylalkyl group".
[0080] [Chemical formula 8]
[0081]
[0082] In formula (5-2), p is an integer of 1 to 3, q is 0, 1 or 2, and p+q is an integer of 1 to 3. It should be noted that the resin composition containing the curable prepolymer may contain a curable prepolymer that is a copolymer of a plurality of monomers having different p and q. In this case, p is preferably 1 to 3 on average, more preferably 2 to 3, and further preferably 2.0 to 2.5 on average. In addition, q is preferably 0.3 to 1 on average, and further preferably 0.5 to 0.8 on average. It should be noted that in formula (5-2), the indene ring, the vinylbenzyl group and the arylalkyl group may each have a substituent.
[0083] In the formula (5-2), the vinylbenzyl group and the arylalkyl group may be directly bonded to a carbon atom at any of the 1-position, 2-position and 3-position of the indene ring.
[0084] In formula (5-2), the methyl group of the vinylbenzyl group may be in any of the ortho, meta and para positions, preferably in the meta or para position. When the polymer is obtained using two or more monomers, it may be a mixture of an ortho-body, a meta-body and a para-body. In this case, a combination of a meta-body and a para-body is preferred, and the mass ratio of the meta-body to the para-body is preferably 40:60 to 60:40.
[0085] The curable prepolymers exemplified above can be homopolymers or copolymers. As homopolymers, it can be a homopolymer of a unit with vinylbenzyl and indene ring. As copolymers, it can be a copolymer comprising more than 2 units with vinylbenzyl and indene ring, a copolymer comprising 1 or more units comprising vinyl and a unit comprising indene ring, a copolymer of these copolymers and other units, etc. It should be noted that, in order to be set to lower dielectric constant and low dielectric loss tangent, the curable prepolymer may not include other units except the unit with vinylbenzyl and indene ring, the unit with vinylbenzyl and the unit with indene ring. From such a viewpoint, in the curable prepolymer, relative to the gross mass of the curable prepolymer, the total amount of the unit with vinylbenzyl and indene ring, the unit with vinylbenzyl and the unit with indene ring is preferably more than 50% by mass, preferably more than 60% by mass, more than 80% by mass or more than 90% by mass. In the curable prepolymer, the total amount of units having a vinylbenzyl group and an indene ring is preferably 50% by mass or more, more preferably 60% by mass or more, 80% by mass or more, or 90% by mass or more, relative to the total mass of the curable prepolymer.
[0086] Although the curable prepolymers exemplified above may have substituents, since the curable prepolymers are more preferably hydrocarbon compounds, the curable prepolymers may not have polar groups. As polar groups, ester bonds (-CO-O-), ether bonds (-CO-) and the like may be mentioned. In addition, from the viewpoint of dielectric properties, the curable prepolymers may not contain heteroatoms. As heteroatoms, oxygen atoms, nitrogen atoms, sulfur atoms and the like may be mentioned. Among them, the curable prepolymers preferably do not contain oxygen atoms.
[0087] Hereinafter, the synthetic method of curable prepolymer is described. Curable prepolymer can be obtained, for example, by polymerizing a compound containing a vinylbenzyl group and an indene ring. In other examples, curable prepolymer can also be obtained by copolymerizing a compound having a vinylbenzyl group with a compound having an indene ring. In addition, in other examples, curable prepolymer can also be obtained by introducing a vinylbenzyl group and an indene ring into a polymer backbone. Hereinafter, the method of polymerizing a compound containing a vinylbenzyl group and an indene ring is described. It should be noted that curable prepolymer is not limited to the substances synthesized by these synthetic methods.
[0088] First, an example of a method for synthesizing a vinylbenzyl compound is described. As a method for synthesizing the vinylbenzyl compound represented by the above formula (5-1) among the vinylbenzyl compounds, for example, a method of reacting indene with styrene having a halomethyl group in the presence of a basic compound can be mentioned. As styrene having a halomethyl group, for example, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, etc. can be mentioned, and they can be one or a mixture of two or more. The ratio of styrene having a halomethyl group to 1 mol of indene can be, for example, in the range of 1 to 3 mols, or in the range of 2 to 3 mols, or in the range of 2.0 to 2.5 mols. As basic compounds, alkali metal hydroxides, alkali metal alkoxides, etc. can be mentioned.
[0089] In addition, as a method for synthesizing the vinylbenzyl compound represented by the above formula (5-2) among the vinylbenzyl compounds, for example, there can be mentioned a method of reacting indene, styrene having a halomethyl group and an aryl compound having a halomethyl group (excluding styrene having a halomethyl group) in the presence of a basic compound. Examples of styrene having a halomethyl group include the above substances, which may be a mixture of one or more. Examples of aryl compounds having a halomethyl group include α-chlorotoluene, α-chloro-p-xylene, etc. The ratio of styrene having a halomethyl group to 1 mol of indene may be, for example, in the range of 1 to 3 mol, or in the range of 2 to 3 mol, or in the range of 2.0 to 2.5 mol. The ratio of the aryl compound having a halomethyl group to 1 mol of indene may be, for example, in the range of 0.3 to 1 mol, or in the range of 0.5 to 0.8 mol. The total molar number of styrene having a halomethyl group and the aryl compound having a halomethyl group may be 1.5 to 3 mol, 2 to 3 mol, or 2.5 to 2.9 mol per 1 mol of indene. Examples of the basic compound include the above-mentioned basic compounds.
[0090] A phase transfer catalyst may be used in the above reaction. As a phase transfer catalyst, for example, tetra-n-butylammonium bromide may be mentioned. The reaction may be carried out by solution polymerization. The reaction may be carried out, for example, under heating and stirring. A polymerization inhibitor may be added to the reaction system. The obtained product may be purified by known methods such as concentration, reprecipitation, and washing as needed.
[0091] In the method for synthesizing a curable prepolymer, the vinylbenzyl compound may be used alone or in combination of two or more. For example, in the method for synthesizing a vinylbenzyl compound represented by the above formula (5-1) or (5-2), a compound in which a vinylbenzyl group is directly bonded to at least one carbon atom at the 1-position, 2-position, and 3-position of an indene ring is synthesized, but a mixture of two or more isomers of vinylbenzyl compounds having different bonding sites may be provided.
[0092] Next, a method for polymerizing a vinyl benzyl compound to obtain a curable prepolymer is described. The polymerization of the vinyl benzyl compound is preferably carried out by free radical polymerization in a manner that no polar component is generated in the reaction product. The free radical polymerization can be carried out using a free radical polymerization initiator. The polymerization can be carried out by solution polymerization, and the polymerization solvent is not particularly limited. For example, one or a combination of two or more organic solvents used in the resin composition described later can be used as the polymerization solvent.
[0093] The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator, and a thermal radical polymerization initiator is preferred. The radical polymerization initiator is not particularly limited, and examples thereof include azo-based polymerization initiators and organic peroxide-based polymerization initiators.
[0094] Examples of the azo polymerization initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionic acid)dimethyl ester, 1,1'-azobis(methyl cyclohexylcarboxylate), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 4,4'-azobis(3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl 4-cyanopentanoate), and 1,1'-azobis(cyclohexane-1-carbonitrile).
[0095] Examples of the organic peroxide polymerization initiator include diisopropylbenzene peroxide, dibenzoyl peroxide, 2-butanone peroxide, tert-butyl peroxybenzoate, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, bis(tert-butylperoxyisopropyl)benzene, and tert-butyl hydroperoxide.
[0096] In order to prevent polar components from being mixed into the resin composition, the generation of polar by-products in the polymerization system can be reduced. From such a viewpoint, in the free radical polymerization initiator, a compound with a small amount of oxygen atoms can be used. As such a compound, an azo polymerization initiator is preferred. Among them, in the azo polymerization initiator, it is preferred that the compound does not contain heteroatoms except the two nitrogen atoms (N) of the azo group. For example, the compound shown in the following formula (6) can be cited.
[0097] R 11 -N=NR 12 (6)
[0098] In formula (6), R 11 and R 12 are each independently a hydrogen atom or a monovalent functional group, R 11 and R 12 At least one of R is a monovalent functional group. 11 and R 12 They may be the same or different. The monovalent functional group is preferably a hydrocarbon group, which may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, or an aliphatic hydrocarbon group or an aromatic hydrocarbon group. The monovalent functional group is preferably a saturated or unsaturated aliphatic hydrocarbon group, and preferably an alkyl group.
[0099] The alkyl group may be any of a chain alkyl group and a cyclic alkyl group. The chain alkyl group may be a straight chain alkyl group or a branched chain alkyl group. The cyclic alkyl group may have a substituent bonded to a carbon atom on the ring.
[0100] The alkyl group may be, for example, an alkyl group having 1 to 10 carbon atoms, 3 to 8 carbon atoms, or 4 to 8 carbon atoms. Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, cyclohexyl, methylcyclohexyl, cyclohexylmethyl, heptyl, octyl, isooctyl, 2-ethylhexyl, nonyl, decyl, 1,1',3,3'-tetramethylbutyl, and 2,2',4,4'-tetramethylbutyl.
[0101] Specific examples of the compound represented by formula (6) include 2,2'-azobis(2,4,4-trimethylpentane) and 2,2'-azobis(2,4-dimethylvaleronitrile).
[0102] The amount of the radical polymerization initiator used can be appropriately adjusted according to the desired degree of polymerization of the curable prepolymer. In addition, the amount of the radical polymerization initiator used can be appropriately adjusted according to the number of functions of the vinyl benzyl group of the vinyl benzyl compound. For example, the amount of the radical polymerization initiator used can be 0.01 to 5 parts by mass, 0.1 to 4 parts by mass, or 0.5 to 2 parts by mass relative to 100 parts by mass of the content of the vinyl benzyl compound in the polymerization system.
[0103] In the reaction of polymerizing a curable prepolymer from a vinylbenzyl compound, a polymerization inhibitor, a chain transfer agent, etc. may be used from the viewpoint of adjusting the polymerization degree of the curable prepolymer and leaving an effective amount of unreacted vinylbenzyl groups in the curable prepolymer. Alternatively, the polymerization may be stopped at a time when a curable prepolymer having a certain degree of polymerization is obtained while measuring the weight average molecular weight of the polymerization system.
[0104] Hereinafter, the optional components that may be included in the resin composition are described. The resin composition may include an elastomer as an optional component. Examples of the elastomer include diene elastomers, olefin elastomers, polysulfide elastomers, silicone elastomers, fluorine elastomers, urethane elastomers, ether elastomers, etc. In more detail, examples of diene elastomers include styrene-butadiene rubber (SBR), butadiene rubber (BR), styrene-isoprene rubber, isoprene rubber (IR), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), etc. Examples of the olefin elastomer include butyl rubber (IIR), ethylene-propylene rubber, ethylene-vinyl acetate rubber, chlorosulfonated polyethylene, acrylic rubber, etc. These elastomers may be non-hydrogenated or hydrogenated. Among them, from the viewpoint of low dielectric constant and good heat resistance, styrene-butadiene rubber (SBR) is preferred.
[0105] Styrene-butadiene rubber does not contain oxygen atoms in the molecule, so in the cured product obtained by using the resin composition containing styrene-butadiene rubber, the amount of polar groups can be reduced, and the relative dielectric constant and dielectric loss tangent can be further reduced. In addition, since styrene-butadiene rubber has a benzene ring derived from styrene in the molecule, it has good compatibility with the curable prepolymer having a vinyl benzyl group in the resin composition, and the moldability can be further improved in the obtained cured product.
[0106] Styrene-butadiene rubbers include styrene-butadiene copolymers and styrene-butadiene-styrene copolymers. These may be non-hydrogenated or hydrogenated. In the case of hydrogenated products, the carbon-carbon double bonds of butadiene may be partially or completely saturated. As hydrogenated products, for example, styrene-ethylene-butylene-styrene copolymers and styrene-ethylene-butylene copolymers may be used.
[0107] In styrene-butadiene rubber or its hydrogenated product, from the viewpoint of dielectric properties, the structural unit derived from styrene is preferably 5 to 80% by mass, more preferably 10 to 75% by mass, further preferably 15 to 60% by mass, and further preferably 20 to 45% by mass. In addition, when it is within these ranges, the viscoelasticity of styrene-butadiene rubber or its hydrogenated product also becomes moderate, which can further improve the adhesion of the resin composition to the coated material.
[0108] From the viewpoint of solvent solubility, formability and flexibility, the weight average molecular weight (Mw) of the elastomer is preferably 50,000 to 500,000, more preferably 70,000 to 300,000, and further preferably 100,000 to 200,000. From the viewpoint of solvent solubility, formability and flexibility, the number average molecular weight (Mn) of the elastomer is preferably 10,000 to 200,000, more preferably 30,000 to 150,000, and further preferably 50,000 to 120,000. From the viewpoint of compatibility with the curable prepolymer, the Mw / Mn of the elastomer is preferably 1.0 to 5.0, more preferably 1.5 to 3.5, and further preferably 2.0 to 3.0. The method for measuring the weight average molecular weight (Mw) and number average molecular weight (Mn) of the elastomer is based on the method described above.
[0109] The elastomer may be used alone or in combination of two or more. The elastomer may be contained in an amount of 1 to 80 parts by mass, 10 to 70 parts by mass, 20 to 60 parts by mass, or 30 to 40 parts by mass based on 100 parts by mass of the curable prepolymer.
[0110] In the resin composition, the coating of the curable prepolymer itself has excellent viscosity and excellent formability of the cured product, so the content of the elastomer can be reduced, and the resin composition may not contain the elastomer. On the other hand, in the resin composition, since the curable prepolymer does not have a polar group, there is a trend of good compatibility with the elastomer in the resin composition, and the content of the elastomer can also be increased. In addition, when the weight average molecular weight (Mw) of the curable prepolymer is 50,000 or more, the compatibility with the elastomer is better, and the content of the elastomer can be further increased.
[0111] The resin composition may include a filler as an arbitrary component. As a filler, inorganic fillers and organic fillers, etc. may be mentioned, and from the viewpoint of dielectric properties, inorganic fillers are preferred. As an inorganic filler, for example, silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium oxide, barium titanate, strontium titanate, potassium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, aluminum borate, silicon carbide, mica, beryllium oxide, clay, talc, etc. may be mentioned.
[0112] The shape and size of the inorganic filler are not particularly limited. The average particle size of the inorganic filler can be, for example, 0.01 to 20 μm, 0.1 to 10 μm, or 1 to 5 μm. Here, the average particle size of the inorganic filler is the particle size corresponding to the point of 50% of the cumulative value in the volume-based particle distribution based on the laser diffraction scattering method.
[0113] The filler may be used alone or in combination of two or more. The filler may be 10 to 500 parts by mass, 50 to 400 parts by mass, 100 to 350 parts by mass, or 200 to 300 parts by mass relative to 100 parts by mass of the curable prepolymer. In the case where an elastomer is included in the resin composition, the inorganic filler may be 50 to 400 parts by mass, 100 to 350 parts by mass, or 200 to 300 parts by mass relative to 100 parts by mass of the total amount of the curable prepolymer and the elastomer.
[0114] If the curable prepolymer is liquid, the resin composition can be a solvent-free resin composition containing the curable prepolymer. In addition, the resin composition can contain a curable prepolymer and a solvent. The solvent can adjust the viscosity of the resin composition and further improve the coating property. As the solvent, an organic solvent is preferred.
[0115] Examples of the organic solvent include alcohol solvents such as ethanol, propanol, butanol, methyl cellosolve, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether solvents such as tetrahydrofuran; aromatic hydrocarbon solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethyl sulfoxide; ester solvents such as γ-butyrolactone, etc. The organic solvent may be used alone or in combination of two or more.
[0116] When the resin composition contains a solvent, the solid content may be 10 to 80 mass %, 30 to 70 mass %, or 40 to 60 mass % based on the total mass of the resin composition, taking components other than the solvent as solid content.
[0117] The resin composition may further include additives other than the above-mentioned components within the scope of not impairing the effect of the present invention. As additives, for example, curing agents, curing accelerators, flame retardants, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, pigments, colorants, lubricants, etc. may be cited. In addition, thermosetting resins and thermoplastic resins other than the above descriptions may be added to the resin composition. The resin composition may include a free radical polymerization initiator or its by-products from the polymerization of the prepolymer. In addition, in the resin composition, free radical polymerization initiators may also be added as curing accelerators.
[0118] The method for making the resin composition is not particularly limited. The resin composition of one embodiment is not limited by the method for making, and its features are as described in the present invention. As an example of a method for making a resin composition, a curable prepolymer can be mixed alone or combined with any component to obtain a resin composition. For example, a curable prepolymer can be dissolved or dispersed in a solvent, and an elastomer, a filler, additives other than them, etc. can be added as needed to mix to obtain a resin composition. The mixing order, temperature, time and other conditions of each component are not particularly limited, and can be appropriately set according to the type of raw materials, manufacturing scale, manufacturing equipment, etc.
[0119] "solidified matter"
[0120] According to one embodiment, a cured product of a resin composition can be provided. The details of the resin composition are as described above. In addition, since the cured product is provided using a resin composition comprising a curable prepolymer, the viscosity of the coating of the resin composition is improved, and the generation of molding marks in the cured product can be reduced. In addition, in the case of providing a cured product using a resin composition comprising a curable prepolymer and an elastomer, by making the weight average molecular weight (Mw) of the curable prepolymer be 50,000 or more, the compatibility can be improved in the resin composition, and the occurrence of layer separation caused by uneven components can be reduced in the obtained cured product.
[0121] The relative dielectric constant (Dk) of the cured product of the resin composition at 25°C and 10 GHz is preferably 4.0 or less, more preferably 3.5 or less, and further preferably 3.2 or less. In more detail, the relative dielectric constant (Dk) of the cured product of the resin composition at 25°C and 10 GHz may be 3.20 or less, 3.15 or less, or 3.10 or less. The smaller the relative dielectric constant (Dk) of the cured product of the resin composition at 25°C and 10 GHz, the more preferred it is, and its lower limit is not particularly limited, and considering the balance with other physical properties, it may be, for example, 2.3 or more, or 2.4 or more.
[0122] The dielectric loss tangent (Df) of the cured product of the resin composition at 25°C and 10 GHz is preferably 0.0080 or less, more preferably 0.0012 or less, and further preferably 0.0011 or less. The smaller the dielectric loss tangent (Df) of the cured product of the resin composition at 25°C and 10 GHz, the more preferred it is. The lower limit is not particularly limited, and in consideration of the balance with other physical properties, it may be, for example, 0.0001 or more.
[0123] In addition, when the resin composition does not contain a filler, the relative dielectric constant (Dk) of the cured product of the resin composition at 25°C and 10GHz is preferably 3.0 or less, more preferably 2.7 or less, and further preferably 2.5 or less. In more detail, the relative dielectric constant (Dk) of the cured product of the resin composition at 25°C and 10GHz may be 2.70 or less, 2.65 or less, or 2.60 or less. In addition, when the resin composition does not contain a filler, the dielectric loss tangent (Df) of the cured product of the resin composition at 25°C and 10GHz is preferably 0.0020 or less, more preferably 0.0014 or less, further preferably 0.0012 or less, and further preferably 0.0010 or less.
[0124] In the present invention, the relative dielectric constant (Dk) and dielectric loss tangent (Df) at 25°C and 10 GHz are measured at 25°C in a 10 GHz band according to the SPDR method (split dielectric resonator). The measuring device can use the "PNA Network Analyzer N5227A" (trade name) of Agilent Technologies. The sample used for the measurement of the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition is the following sample: a cured product obtained using the resin composition is formed into a sample with a thickness of 1 cm and 5 cm×10 cm.
[0125] The sample to be measured for the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition is a sample in which the resin composition is cured to a C-stage state in JIS K 6800 (1985).
[0126] "Prepreg"
[0127] According to one embodiment, a prepreg containing a resin composition or a semi-cured product of a resin composition can be provided. The details of the resin composition are as described above.
[0128] The prepreg may contain a resin composition or a semi-cured product of the resin composition and a fiber base material. In the prepreg, the curable prepolymer may be in an uncured state, or the curable prepolymer may be in a partially or completely semi-cured state.
[0129] Prepregs can be obtained, for example, by applying a resin composition to a fiber substrate and drying it. In another method, prepregs can be obtained by impregnating a fiber substrate with a resin composition and drying the fiber substrate impregnated with a curable prepolymer. Drying is preferably carried out at a temperature above the temperature at which volatile components such as solvents that may be contained in the resin composition are removed, and can also be carried out within a temperature range at which the curable prepolymer contained in the resin composition is semi-cured, depending on the application. In addition, drying can be adjusted in a manner that the curable prepolymer contained in the resin composition is not completely cured. From this point of view, the drying temperature can be 80 to 200°C, and the drying time can be 1 to 30 minutes depending on the drying temperature and the drying device, its scale, etc.
[0130] In the present invention, when referring to the semi-cured material of the curable prepolymer, it refers to the state in which the vinylbenzyl groups contained in the curable prepolymer partially participate in the curing reaction, and the remaining vinylbenzyl groups remain. The semi-cured material of the curable prepolymer having the vinylbenzyl group is in a state in which the curing reaction can continue by further performing a heat treatment, etc. In the present invention, as an index of the semi-cured material, the B-stage state in JIS K 6800 (1985) can be cited.
[0131] The fiber substrate can be any of woven fabrics, knitted fabrics and non-woven fabrics. The fiber substrate can be provided in the form of chopped strand mats, rovings and the like. The fiber material can be any of inorganic fibers and organic fibers. As inorganic fibers, glass fibers, carbon fibers and the like can be mentioned. As glass fibers, E glass, NE glass, D glass, S glass, Q glass and the like can be mentioned. As organic fibers, polyimide, polyester, tetrafluoroethylene and the like can be mentioned. The fiber substrate can be a single fiber among them, or a blended fiber of two or more thereof. From the viewpoint of dielectric properties and heat resistance, the fiber substrate is preferably an inorganic fiber, more preferably a glass fiber.
[0132] The fiber substrate can be appropriately selected according to the purpose of the prepreg, and a sheet-like fiber substrate is preferred. As the sheet-like fiber substrate, for example, various sheet-like fiber substrates used in known laminated boards for electrical insulating materials can be used. The thickness of the sheet-like fiber substrate is not particularly limited, and for example, it is preferably 0.02 to 0.5 mm. Here, the thickness is the thickness measured at 5 points at equal distances on the entire surface of the sheet-like fiber substrate, and is set as the arithmetic mean of the 5 points.
[0133] In the prepreg, the total mass of the curable prepolymer and the elastomer can be 20 to 90% by mass, or 30 to 80% by mass, relative to the total mass of the curable prepolymer, the elastomer, and the fiber substrate. However, there is also a case where the mass of the elastomer is 0% by mass. In these ranges, the resin can be more easily impregnated into the fiber substrate in the prepreg. In addition, the process of assembling the prepreg into a molded product and curing it can be more easily performed.
[0134] "Resin film"
[0135] According to one embodiment, a resin film containing a resin composition or a semi-cured product of a resin composition can be provided. The details of the resin composition are as described above.
[0136] Resin film refers to an article in which a resin composition is formed into a film-like state. In the resin film, the curable prepolymer can be in an uncured state, but the curable prepolymer can also be partially or completely in a semi-cured state. By utilizing heat treatment etc. to cure the resin film, a cured product can be obtained.
[0137] The resin film can be obtained, for example, by applying a resin composition to a coated material and drying it. Drying can be carried out in the same manner as in the above-mentioned method for manufacturing prepregs. It is also possible to provide a product in the form of a combination of a resin film and a coated material after drying the resin film on the coated material. For example, in this method, a resin film can be provided as an insulating layer in a printed wiring board. In other methods, it is also possible to provide the resin film as a product after drying the resin film on the coated material, peeling the resin film from the coated material.
[0138] The coated material may be any of an inorganic substrate and an organic substrate, or may be a glass substrate, a metal foil, a metal plate or other metal substrate, a plastic plate, a plastic film or other plastic substrate, a paper substrate, or the fiber substrate described in the above prepreg. In order to provide the resin film to be peeled off from the coated material, a coated material having a release layer formed on the surface may be used.
[0139] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the prepreg and the resin film are not particularly limited, but are preferably independently within the numerical ranges of the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition described above.
[0140] "Metal-clad laminate"
[0141] According to one embodiment, a metal-clad laminate having a cured product of a resin composition and a metal foil can be provided. The details of the resin composition are as described above.
[0142] The metal-clad laminate preferably has a resin cured material layer including a resin cured material and a metal foil formed on at least one side of the resin cured material layer. The resin cured material layer includes a cured material of a resin composition, but may also be a cured material of the above-mentioned prepreg or resin film. As a more useful application, a metal foil is formed on at least one side of the cured material of the prepreg, and more preferably, a metal foil is formed on both sides of the cured material of the prepreg. The resin cured material layer may form a metal foil on at least one side of a sheet-like prepreg, or may stack more than two sheet-like prepregs, and form a metal foil on at least one side of the outermost surface of the laminate. As a more useful application, the metal-clad laminate is a laminate in which more than two sheet-like prepregs are stacked and a metal foil is formed on both sides of the laminate.
[0143] The metal-clad laminate can be manufactured, for example, by configuring a metal foil on one or both sides of a sheet-like prepreg, and then performing heat and pressure molding. As a result, the curing reaction of the sheet-like prepreg proceeds, and a cured product of the prepreg can be obtained. When performing heat and pressure molding, only one prepreg can be used, or more than two prepregs can be stacked and used. The heating and pressing conditions are not particularly limited, and for example, the temperature can be set to 100 to 300°C, the time can be 10 to 300 minutes, and the pressure can be 1.5 to 5MPa. In addition, after heating and pressing, in order to further perform the curing of the prepreg, reheating can be performed. The reheating temperature at this time can be 100 to 300°C. As a heating and pressing method, for example, an autoclave molding machine, a multi-stage press machine, a multi-stage vacuum press machine, a continuous molding machine, etc. can be used.
[0144] The metal of the metal foil is not particularly limited, and examples thereof include copper, nickel, aluminum, gold, silver, platinum, molybdenum, ruthenium, tungsten, iron, titanium, chromium, and alloys containing two or more of these metal elements. Industrially, it can be a single metal of copper, nickel, or aluminum. By using copper as the metal foil, a copper-clad laminate can be provided.
[0145] The dielectric properties of the cured resin in a state where the metal foil is removed from the metal-clad laminate (also referred to as the relative dielectric constant of the metal-clad laminate or the dielectric loss tangent of the metal-clad laminate) are preferably as follows.
[0146] The relative dielectric constant (Dk) of the metal-clad laminate is preferably 4.0 or less at 25°C and 10 GHz, more preferably 3.5 or less, and further preferably 3.2 or less. In more detail, the relative dielectric constant (Dk) of the metal-clad laminate can be 3.20 or less, 3.15 or less, or 3.10 or less at 25°C and 10 GHz. The smaller the relative dielectric constant (Dk) of the metal-clad laminate at 25°C and 10 GHz, the more preferred it is, and its lower limit is not particularly limited. Considering the balance with other physical properties, it can be, for example, 2.3 or more, or 2.4 or more.
[0147] The dielectric loss tangent (Df) of the metal-clad laminate is preferably 0.0080 or less at 25°C and 10 GHz, more preferably 0.0012 or less, and further preferably 0.0011 or less. The dielectric loss tangent (Df) of the metal-clad laminate is preferably as small as possible at 25°C and 10 GHz, and its lower limit is not particularly limited, and in consideration of the balance with other physical properties, it may be, for example, 0.0001 or more.
[0148] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the metal-clad laminate are determined as described in the cured product of the resin composition. The sample for the determination of the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the metal-clad laminate is immersed in an etching solution to remove the metal foil from the cured resin, and an evaluation substrate with a thickness of 0.2 mm and 5 cm × 10 cm is cut out from the test piece from which the metal foil is removed for use. In the case of a copper-clad laminate, an ammonium persulfate 10 mass % solution is used as the etching solution.
[0149] "Printed Circuit Board"
[0150] According to one embodiment, a printed wiring board having a cured product of a resin composition can be provided. The details of the resin composition are as described above.
[0151] In a printed wiring board, the cured product of a resin composition can be manufactured by using a resin composition, a prepreg, a resin film, a metal-clad laminate, or a combination thereof. For example, a cured product of a prepreg can be used to make a substrate for a printed wiring board, thereby providing a printed wiring board. In addition, in other examples, a metal-clad laminate can be used as a substrate for a printed wiring board to provide a printed wiring board. Details about prepreg, resin film, and metal-clad laminate are as described above.
[0152] The printed wiring board may be either a single-layer printed wiring board or a multi-layer printed wiring board.
[0153] "Semiconductor Package"
[0154] According to one embodiment, a semiconductor package having a printed wiring board and a semiconductor element can be provided. The details of the printed wiring board are as described above. The semiconductor package can be manufactured by mounting a semiconductor element, a memory, etc. on the printed wiring board using a known method.
[0155] Examples of the embodiments are given below, but the present invention is not limited to the following embodiments.
[0156] <1> A resin composition comprising a curable prepolymer having a vinylbenzyl group and an indene ring and having a weight average molecular weight of 50,000 or more.
[0157] <2> according to <1> The resin composition described in , wherein the weight average molecular weight of the curable prepolymer is 150,000 or more.
[0158] <3> according to <1> or <2> The resin composition described in , wherein the curable prepolymer comprises a structural unit having an indene ring and a vinylbenzyl group directly bonded to a carbon atom of the indene ring.
[0159] <4> according to <1> ~ <3> The resin composition according to any one of the above, wherein the curable prepolymer comprises a structural unit derived from a vinylbenzyl compound having 1 to 3 vinylbenzyl groups and 1 indene ring in one molecule.
[0160] <5> according to <1> ~ <4> The resin composition according to any one of the above, further comprising a filler.
[0161] <6> A prepreg comprising the above <1> ~ <5> The resin composition according to any one of the above or a semi-cured product of the resin composition.
[0162] <7> A resin film comprising the above <1> ~ <5> The resin composition according to any one of the above or a semi-cured product of the resin composition.
[0163] <8> A metal-clad laminate having the above <1> ~ <5> A cured product of the resin composition according to any one of claims , and a metal foil.
[0164] <9> A printed circuit board having the above <1> ~ <5> A cured product of the resin composition according to any one of the above.
[0165] <10> A semiconductor package having the above <9> A printed wiring board and a semiconductor element described in.
[0166] Example
[0167] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples. Tables 1 to 6 show the compositions of the resin compositions and the evaluation results.
[0168] "Method for determining weight average molecular weight (Mw)"
[0169] The weight average molecular weight is converted by gel permeation chromatography (GPC) based on a calibration curve using standard polystyrene. The calibration curve uses standard polystyrene: TSKstandard POLYSTYRENE (model: A-2500, A-5000, F-20, F-80) (Tosoh Corporation, trade name), and is approximated by a cubic formula. The measurement conditions of GPC are shown below.
[0170] Apparatus: High-speed GPC apparatus HLC-8320GPC (Tosoh Corporation, trade name) Detector: Ultraviolet absorption detector UV-8320 (Tosoh Corporation, trade name)
[0171] Column: guard column; TSKgel guardcolumn Super(HZ)-M+, column; TSKgel SuperMultiporeHZ-M (2 pieces), reference column; TSKgel SuperH-RC (2 pieces) (all Tosoh Corporation, trade names)
[0172] Column size: 4.6×20mm (guard column), 4.6×150mm (column), 6.0×150mm (reference column)
[0173] Eluent: Tetrahydrofuran
[0174] Sample concentration: 10mg / 1mL
[0175] Injection volume: 20μL or 2μL
[0176] Flow rate: 0.35mL / min
[0177] Measurement temperature: 40℃
[0178] "Preparation of vinylbenzyl monomer (1)"
[0179] In a 500 mL reaction container equipped with a stirring device, a thermometer, a reflux tube and a nitrogen blowing port, 35.6 parts by mass of indene, 101.2 parts by mass of chloromethylstyrene described below, 7.1 parts by mass of tetra-n-butylammonium bromide (manufactured by Kanto Chemical Co., Ltd.) as a phase transfer catalyst, 0.1 parts by mass of phenothiazine as a polymerization inhibitor, and 77.6 parts by mass of toluene as a solvent were placed, and the mixture was heated and stirred at 40° C. while nitrogen was blown in at a flow rate of 50 mL / min.
[0180] Chloromethylstyrene "CMS-P": AGC Seimi Chemical Co., Ltd., a mixture of meta-form and para-form, with the meta-form content being 50% by mass and the para-form content being 50% by mass.
[0181] Next, 46.5 parts by mass of an aqueous solution of the following basic compound was added dropwise over 20 minutes, and the mixture was further stirred at 60° C. for 9 hours. It should be noted that nitrogen was continuously blown in during the reaction. After cooling to room temperature (about 25° C.) and neutralizing with a 10% aqueous hydrochloric acid solution, the mixture was washed twice with pure water, toluene was distilled off under reduced pressure, and the obtained viscous liquid was washed with methanol and then vacuum dried to obtain a vinyl benzyl monomer (1).
[0182] Aqueous solution of alkaline compound: an aqueous solution of sodium hydroxide having a concentration of 48% by mass, manufactured by Kanto Chemical Co., Ltd.
[0183] pass 1 H-NMR analysis confirmed that the obtained vinylbenzyl monomer (1) has a structure of a vinylbenzyl group directly bonded to the carbon atom at position 1, position 3, or a combination of these of indene. In addition, according to gel permeation chromatography (GPC) analysis, the vinylbenzyl monomer (1) is a mixture of a monomer having two vinylbenzyl groups and a monomer having three vinylbenzyl groups. In the case where the vinylbenzyl monomer has three vinylbenzyl groups, it is confirmed that there are two vinylbenzyl groups directly bonded to the carbon atom at position 1 of the indene ring and one vinylbenzyl group directly bonded to the carbon atom at position 3. The weight average molecular weight (Mw) of the vinylbenzyl monomer (1) is 500. The weight average molecular weight (Mw) is measured by the above method.
[0184] "Manufacturing of prepolymer (1)"
[0185] The vinylbenzyl monomer (1) obtained above was mixed with toluene to a solid content of 60% by mass. 4000 g of the vinylbenzyl monomer (1) having a solid content of 60% by mass and 24 g of the following azo polymerization initiator were added to a 5 L separable flask, and stirred at 200 rpm for 1 minute. Then, heating was performed while nitrogen was circulated at 400 mL / min, and heating was performed at 110°C ± 10°C.
[0186] When the Mw of the produced curable prepolymer (1) reached the target value between 5,000 and 500,000, heating was stopped and the mixture was cooled to obtain solutions of curable prepolymers (1) of various Mw values shown in the table. The weight average molecular weight (Mw) was measured by the above method.
[0187] Azo polymerization initiator: 2,2′-azobis(2,4,4-trimethylpentane) (“VR-110” (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (10-hour half-life temperature: 110° C.).
[0188] "Preparation of vinylbenzyl monomer (2)"
[0189] In a 500 mL reaction container equipped with a stirring device, a thermometer, a reflux tube and a nitrogen blowing port, 35.6 parts by mass of indene, 101.2 parts by mass of the above-mentioned chloromethylstyrene, 24.1 parts by mass of α-chloro-p-xylene, 9.1 parts by mass of tetra-n-butylammonium bromide (manufactured by Kanto Chemical Co., Ltd.) as a phase transfer catalyst, 0.1 parts by mass of phenothiazine as a polymerization inhibitor, and 91.6 parts by mass of toluene as a solvent were placed, and the mixture was heated and stirred at 40° C. while nitrogen was blown in at a flow rate of 50 mL / min.
[0190] Next, 122.9 parts by mass of an aqueous solution of the above-mentioned basic compound was added dropwise over 20 minutes, and the mixture was further stirred at 60°C for 9 hours. It should be noted that nitrogen was continuously blown in during the reaction. The mixture was cooled to room temperature (about 25°C), neutralized with a 10% aqueous hydrochloric acid solution, washed twice with pure water, toluene was distilled off under reduced pressure, and the obtained viscous liquid was washed with methanol and then vacuum dried to obtain a vinyl benzyl monomer (2).
[0191] For the obtained vinylbenzyl monomer (2), by 1 H-NMR analysis showed that a reaction occurred in which a vinylbenzyl group or a methylbenzyl group was bonded to any one or more positions of the 1 to 3 positions of the indene ring. In addition, gel permeation chromatography (GPC) analysis confirmed that the vinylbenzyl monomer (2) was a mixture of a monomer (1-substituent) into which one substituent selected from vinylbenzyl and methylbenzyl was introduced, a monomer (2-substituent) into which two substituents were introduced, and a monomer (3-substituent) into which three substituents were introduced. The weight average molecular weight (Mw) of the vinylbenzyl monomer (2) was 323. The weight average molecular weight (Mw) was measured by the above method.
[0192] "Manufacturing of prepolymer (2)"
[0193] The vinylbenzyl monomer (2) obtained above was mixed with toluene to obtain a solid content of 60% by mass. 4000 g of the vinylbenzyl monomer (2) having a solid content of 60% by mass and 24 g of the azo polymerization initiator were added to a 5 L separable flask and stirred at 200 rpm for 1 minute. Then, heating was performed while nitrogen was circulated at 400 mL / min at 110°C ± 10°C.
[0194] When the Mw of the produced curable prepolymer (2) reached the target value between 5,000 and 500,000, heating was stopped and the mixture was cooled to obtain a solution of the curable prepolymer (2) having the Mw shown in the table. The weight average molecular weight (Mw) was measured by the above method.
[0195] "Preparation of resin composition"
[0196] The components shown in the table were blended with toluene in the amounts shown in the table, stirred and mixed at 25° C., and resin compositions of Examples and Comparative Examples having a solid content concentration of about 60% by mass were prepared. In the table, the unit of the blending amount of each component is parts by mass, and in the case of a solution, it refers to parts by mass converted to solid content.
[0197] The ingredients used are as follows.
[0198] Vinylbenzyl monomer (1): The monomer produced above was used.
[0199] Curable prepolymer (1): The curable prepolymer produced as described above was used.
[0200] Curable prepolymer (2): The curable prepolymer produced as described above was used.
[0201] Elastomer 1: styrene·ethylene·butylene·styrene copolymer (SEBS), styrene content: 20% by mass, trade name "MD-1648", manufactured by Kraton.
[0202] Elastomer 2: styrene·ethylene·butene copolymer (SEB), styrene content: 34% by mass, trade name "MD-6951", manufactured by Kraton.
[0203] Silica filler: average particle size 2 μm.
[0204] "Prepreg production"
[0205] The obtained resin composition was applied by impregnation to a glass cloth having a thickness of 0.5 mm (manufactured by Nitto Bosho Co., Ltd.), and dried by heating at 130° C. for 4 minutes to obtain a prepreg having a solid content of 70% by mass derived from the resin composition.
[0206] "Manufacturing of copper-clad laminates"
[0207] Electrolytic copper foil ("3EC-M3-VLP-18" (trade name) manufactured by Mitsui Mining & Smelting Co., Ltd.) with a thickness of 18 μm was overlapped on both sides of the obtained prepreg so that the rough surface was bonded to the prepreg, and heated and pressed for 80 minutes under vacuum pressing conditions of 230°C and 3 MPa, thereby producing a copper-clad laminate.
[0208] "Evaluation methods and measurement methods"
[0209] Evaluation and measurement were performed as follows, and the results are shown in the table.
[0210] (Adhesion of prepreg)
[0211] The resin composition was impregnated and coated on a glass cloth having a thickness of 30 μm, and dried at 130°C for 10 minutes to obtain a prepreg. At this time, the film thickness of the dried prepreg was made to be 50 μm. After drying, the surface of the prepreg was touched by hand in an uncured state, and a sensory evaluation was performed on the presence or absence of stickiness. The evaluation criteria are as follows. It should be noted that the benchmark for non-stickiness is set to be equivalent to the prepreg of Example 1.
[0212] A: No stickiness.
[0213] B: Sticky.
[0214] (Compatibility of resin composition)
[0215] The resin composition was placed in a transparent threaded tube and allowed to stand for 1 hour, and the phase separation of the resin composition was visually observed. The evaluation criteria were as follows. In addition, the resin composition was dripped into an aluminum cup and dried in a dryer at 170°C for 30 minutes to solidify it. Visually observe whether the solidified resin was separated in spots. In the embodiments and comparative examples where phase separation of the resin composition was not observed, the resin was not separated in spots during coating.
[0216] A: Phase separation of the resin composition was not observed.
[0217] B: Phase separation of the resin composition was observed.
[0218] (Formability of copper-clad laminate)
[0219] After the copper-clad laminate manufactured above is cut into 250 mm square, the end is cut off by about 1 cm. Then, the copper foil on the surface of the copper-clad laminate is etched to obtain an evaluation substrate. Visual observation is made on the end and surface of the evaluation substrate to see if there is separation of resin or silica filler. In addition, visual observation is made on the surface of the evaluation substrate to see if there are stripes. The evaluation criteria are as follows.
[0220] A: No streaks were observed on the surface of the evaluation substrate, and no separation of the resin or the silica filler was observed.
[0221] B: Streaks were observed on the surface of the evaluation substrate, but separation of the resin or the silica filler was not observed.
[0222] C: Separation of the evaluation substrate was observed.
[0223] (Dielectric properties of cured product of resin composition)
[0224] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition are measured at 10 GHz band and 25 ° C according to the SPDR method (split dielectric resonator). The measuring device uses the "PNA Network Analyzer N5227A" (trade name) of Agilent Technologies. The sample of the measurement object of the relative dielectric constant (Dk) and dielectric loss tangent (Df) of the cured product of the resin composition is obtained by curing the resin composition to become the state of the C-stage in JIS K 6800 (1985). Specifically, the solvent of the resin composition is dried under the conditions of 130 ° C and 10 minutes, and the obtained resin powder is added to the mold made of PTFE for compression molding. The pressing conditions are set to the same conditions as "the production of copper-clad laminates", and a sample of a size of 1 cm and 5 cm × 6 cm is prepared.
[0225] [Table 1]
[0226] [Table 1] Composition and evaluation results
[0227]
[0228] [Table 2]
[0229] [Table 2] Composition and evaluation results
[0230]
[0231] [Table 3]
[0232] [Table 3] Composition and evaluation results
[0233] [Table 4]
[0234] [Table 4] Composition and evaluation results
[0235] [Table 5]
[0236] [Table 5] Composition and evaluation results
[0237]
[0238] [Table 6]
[0239] [Table 6] Composition and evaluation results
[0240]
[0241] As shown in the table, it can be seen that the use of a resin composition containing a curable prepolymer having a weight average molecular weight (Mw) of 50,000 or more improves the adhesion of the prepreg and the formability of the copper-clad laminate.
[0242] Industrial Applicability
[0243] The resin composition of some embodiments of the present invention can be used, for example, as a copper-clad laminate or other metal-clad laminate, a substrate material for a printed wiring board, etc. in mobile communication devices represented by smartphones, their base station devices, network infrastructure equipment such as servers and routers, and electronic devices such as large computers that expect higher signal speeds and larger capacity.
[0244] The present invention is related to the subject matter described in Japanese Patent Application No. 2023-085360 filed on May 24, 2023, and all of their disclosures are incorporated herein by reference. It should be noted that in addition to the contents already described, various modifications and changes may be made to the above-mentioned embodiments without departing from the novel and advantageous features of the present invention. Therefore, all such modifications and changes are included in the attached technical solutions.
Claims
1. A resin composition comprising a curable prepolymer containing a vinylbenzyl group and an indene ring and having a weight average molecular weight of 50,000 or more.
2. The resin composition according to claim 1, wherein The weight average molecular weight of the curable prepolymer is greater than 150,000.
3. The resin composition according to claim 1, wherein The curable prepolymer includes a structural unit having an indene ring and a vinylbenzyl group directly bonded to a carbon atom of the indene ring.
4. The resin composition according to claim 1, wherein The curable prepolymer includes a structural unit derived from a vinylbenzyl compound having 1 to 3 vinylbenzyl groups and 1 indene ring in one molecule. The resin composition according to claim 1 , further comprising a filler. 6 . A prepreg comprising the resin composition according to claim 1 or a semi-cured product of the resin composition. 7 . A resin film comprising the resin composition according to claim 1 or a semi-cured product of the resin composition. 8 . A metal-clad laminate comprising a cured product of the resin composition according to claim 1 and a metal foil. 9 . A printed wiring board comprising a cured product of the resin composition according to claim 1 . 10 . A semiconductor package comprising the printed wiring board according to claim 9 and a semiconductor element.
Citation Information
Patent Citations
Thermosetting resin composition and electronic part using the same
JP2007119531A
Inspection system
JP2023085360A